Webinars for Teachers: A Lived Experience for Developing Capability in These Challenging Times - Aplacador, Rose Ann A.; Abada, Rona B.; Delavin, Elreen A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The sudden force shut down of all educational institutes across the country due to COVID19 pandemic is truly a great challenge on how to continue resiliency in education. As response, educational institutions conducted webinars to enhance the faculty capabilities in these challenging times. Thus, the purpose of this paper is to explore the lived experiences of teachers who attended webinars during the pandemic. An interview was conducted to ten participants from Aroroy National High School. Purposive sampling technique was employed. Researchers used self-made questionnaire with open ended questions and thematic analysis is applied in analyzing the data. Five major themes where identified: (1) Developed Capabilities; (2) Significance of webinars in current situation; (3) Best Practices; (4) Suggestions for Smooth Running; and (5) Plan for utilization and enhancement of learnt knowledge and skills. These themes shows that webinars positively affects the teachers during pandemic. Teachers developed their teaching skills, technical and managerial skills and emotional quotient through webinars. It was also concluded that educators experience the enormous impact of webinars in their lives when they effectively utilized and shared their learnt knowledge and skills in the webinars. However, it should be considered that in conducting an effective and smooth webinars there must be guidelines to follow. Challenging times will not be as challenging as they are when the goal of webinars to develop faculty capability is successfully planned and achieved.